Description of Rhopalum (s. str.) gulmargense n. sp. with a key to the Indian species of the subgenus Rhopalum Stephens, 1829 s. str. (Hymenoptera: Crabronidae: Crabronini) - Saini, Varun; Dey, Debjani (Zootaxa, 2022)
A new species of the genus Rhopalum is described from India: Rhopalum (s. str.) gulmargense Saini & Dey. A key to the Indian species of the subgenus Rhopalum s. str. and a checklist of all Indian Rhopalum are provided.